Application and Analysis of Big Data Mining in the Foreign Affairs Translation System. (19th November 2022) - Zhang, Chaowei
Abstract : Based on the expansion of scientific and technological capabilities, the trend of global integration has further strengthened, and the relations between countries have become closer and closer. Therefore, the foreign affairs translation system plays a very important role. Many scientific and technological projects have carried out research and analysis around the foreign affairs translation system. Nowadays, the wide variety of data and the complexity of languages in various countries force the processing structure of the foreign affairs translation system to be changed to adapt to the development of big data. In this context, this article studies the foreign affairs translation system based on big data mining technology and designs the application of a new foreign affairs translation system model. The results of the experiment are as follows: (1) The development status of big data mining technology and the problems existing in the current foreign affairs translation system are analyzed, and the research direction of the experiment is determined. The foreign affairs translation system is analyzed according to big data mining technology, which determines the technical guarantee for the research of this article. (2) In keeping with the traditional effective foreign affairs translation system, this article uses big data mining algorithm analysis, the fuzzy c-means clustering algorithm, and the BP neural network algorithm to identify and analyze the problems of the foreign affairs translation model about data analysis ability technology, which quickly and accurately analyzes the problems of the system and optimizes and improves according to the specific problems.